Peran Cash Waqf Linked Sukuk (CWLS) dalam Pemerataan Ekonomi dan Kesejahteraan di Indonesia - Oftafiana, Triya; Nur Laila, Resa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Wakaf was the economic base of the Mamluk dynasty. Wakaf undergoes transformation with the needs of the times because wakaf has a higher value of flexibility compared to zakat, one of which is the use of productive wakafs, like money wakaf. One of the innovations of the money waqf is the presence of Cash Waqf Linked Sukuk where the urgency of the publication of CWLS among other things strengthens the financial economic capacity of the Shariah, strengthens management of the national wahaf institutions, supports the achievement of SDGs, and encourages social investment. This research uses a kind of library research method by gathering data from a variety of literature. The CWLS can prove that even though the wahaf value is not high, it still brings tremendous benefits. From the first publication of the Wakaf chapter to the present day, the CWLS results have contributed significantly to the economic sector or other sectors, such as post-pandemic economic recovery, development and provision of health facilities, empowerment of farmers, and various other tools programmes. CWLS could be a leading product in the future and a reserve for Indonesian economic development.